Analisis Perhitungan Biaya Produksi Menggunakan Metode Activity Base Costing System (ABC System) Menetapkan Harga Jual Karung Plastik Pada PT Citra Prima Lestari Binjai - Nurhabibah Rahmadani Siregar; Sugianto Sugianto; Nur Fadhilah Ahmad Hasibuan (Pusat Riset dan Inovasi Nasional, 2023)
The aim of this research is to analyze the cost of production of PT. Citra Prima Lestari and compare it with the calculation of the cost of production using the Activity Base Costing method, so that it can be a recommendation for companies to calculate the cost of production correctly in determining the selling price of plastic sacks. Research on the cost of production was carried out using a comparative descriptive research method. Data collection techniques in this research include interviews and documentation, as well as primary data and secondary data. The results of the investigation show that the application of production costs using the company's method so far is not appropriate, because the company applies the same production costs for all types of molds compared to applying production costs.